Comparison of various sealers on postoperative pain in single-visit endodontics: A randomized clinical study - Shahnaz Nabi; Riyaz Farooq; Aamir Purra; Fayaz Ahmed (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study is to evaluate the effect of bioceramic-based sealers on postendodontic pain following single-visit endodontics. Materials and Methods: Ninety patients requiring primary endodontic treatment were selected for the study. Patients were treated in single visit endodontically using three different bioceramic-based sealers: Group 1: obturation done using mineral trioxide aggregate plus sealer, Group 2: obturation done using EndoSequence BC sealer, and Group 3: iRoot SP sealer. Postendodontic pain was measured for 48 h postoperatively. Results: No significant difference was found in postendodontic pain scores between the sealers groups. Conclusion: Postendodontic pain was reduced in all treatment groups. Any of the three bioceramic sealers can be used for single-visit endodontics without fear of postoperative pain.